(untitled) (Progressive Agriculture, 2020)
The experiment was conducted at the Horticultural Farm, Bangladesh Agricultural University, Mymensingh during the period from October, 2018 to April, 2019. The present study was aimed at determining the effect of vernalization and doses of boron on seed yield and quality of summer onion. There were three vernalization treatments viz., no vernalization (control), vernalization at 10°C for 25 days and vernalization at10°C for 40 days and four boron treatment viz., 0 kg ha-1, 1 kg ha-1, 2 kg ha-1 and 3 kg ha-1. The two-factor experiment was laid out in the Randomized Complete Block Design with three replications. The results of the experiment showed that the vernalization had significant and positive influence on all the parameters studied. Boron had also significant effects on all the parameters. Interaction between vernalization and boron was significant on all the yield and yield contributing parameters. The highest seed yield (191.01 kg ha-1) was obtained from vernalization at 10°C for 40 days and lowest (137.88 kg/ha) from control. The highest seed yield (255.38kgha-1) was obtained from 3 kg ha-1 boron and lowest (83.48 kg ha-1) from control. When combined effect was considered the highest seed yield (293.36 kgha-1) was obtained from vernalization at 10°C for 40 days with 3 kg ha-1 boron. The lowest value (69.50 kg/ha) was recorded in the control treatment. Progressive Agriculture 30 (4): 371-378, 2019